Early results after transatrial repair of RVOT obstruction including teratology of fallot - Wani, Nasir u din; Muzaffar, Tasneem; Ahangar, Abdul Gani; Sidiq, Mir Mudasir; Lone, Ghulam Nabi; Dar, Abdul Majeed; Lanker, Aadil Mohammed; Bhat, Mohammad Akbar; Singh, Shyam; Hakeem, Zubair; Ganie, Farooq Ahmad (International Journal of Research in Medical Sciences, 2018)
Background: Right ventricular (RV) dysfunction is a significant cause of morbidity and mortality after surgical correction of RVOT obstruction including tetralogy of Fallot (TOF). Transatrial repair avoids a ventriculotomy (in contrast to the transventricular approach) emphasizing maximal preservation of RV structure and function. We have adopted this technique as less traumatic for the right ventricle. This study evaluates the early surgical results of our approach. Methods: Between January 2005 to January 2014, 77 consecutive patients with RVOT obstruction were referred to our unit for surgical therapy. Of these, 14 were unsuitable for repair and underwent aortopulmonary shunting. In the remaining 63 patients (mean age of 2.67±0.38 years), complete transatrial/transpulmonary repair was performed. Previously placed shunts (four patients) were taken down. In all cases, subpulmonary resection and ventricular septal defect (VSD) closure were accomplished transatrially. In 51 patients, the main pulmonary artery was augmented with an autologous pericardial patch. Results: There were 7 (9%) deaths in this series. No patient required permanent pacemaker. Median ICU and hospital stay were 91 hours and 14 days, respectively. At median follow up of 54 (mean 51±12) months, all patients are asymptomatic, with no significant residual lesion. Conclusions: Transatrial/transpulmonary repair of TOF is associated with remarkably low morbidity and mortality in our early experience.